KEGIATAN DONOR DARAH CIVITAS AKADEMIKA SEKOLAH TINGGI ILMU ADMINISTRASI BENGKULU - Gustinii, Gustinii; Pratiwi, Ameitha; Azuwandri, Azuwandri; Putra, M Bima Eka; Dwisnu, Erlian (STIA Bengkulu, 2023)
Blood donation is the activity of a person who voluntarily donates his blood for humanitarian purposes. The purpose of carrying out this blood donor activity is to create a sense of solidarity among people, increase satisfaction with health services, assist the government in providing blood needs for healthy people, and overcome the effects of the spread of disease. Blood donor activity conducted by a person is considered very important, because the blood needs in the Blood Transfusion Unit of Indonesia Red Cross then written UTD PMI in Bengkulu City, only fulfilled about 50% of the existing needs, especially for referrals from several Private Private Hospitals and Houses General Hospital. So that the blood donor activity that was originally done by someone, then done by community group which is in field of Sekolah Tinggi Ilmu Administrasi of Bengkulu.